Molecular Recognition: Evidence of the Redox Role of Ferrocenyl-Imine Derivatives in the Presence of Copper (Ii) Ions - Pavez-Irrazabal, J; Pavez-Irrazabal, J; Godoy-Gonzalez, F; Godoy-Gonzalez, F; Silva-Molina, C; Silva-Molina, C; Agurto-Doren, N; Agurto-Doren, N; Maldonado-Hernandez, T; Maldonado-Hernandez, T; Flores-Vergara, E; Flores-Vergara, E; et al. (Elsevier Ltd, 2019)
The design and development of new selective and sensitive chemosensors for metal ions is an area of intense research activity due to their important roles in medicine, living systems, and the environment. In this work, novel ferrocenyl derivatives functionalized with a crown ether linked via an olefin-imine spacer have been designed as versatile molecular recognizers for a series of metal ions (Na+, Ca+2, Cu2+, and Cd2+). By using UV-vis titrations, these systems showed a high affinity for Cu2+ among other metal ions, nevertheless, with unexpected optical behavior. With Spectroelectrochemical studies and electrochemical titrations we revealed that redox reactions between the ferrocenyl and the imine moieties of the spacer and the copper ions took place. These experimental results prove a redox reaction mechanism between both ferrocenyl and imine moieties in the presence of Cu2+. Therefore, this work puts a notice about the redox reaction that takes place between copper (II) and ferrocenyl-imine derivatives, and this information should be considered when designing metal ion chemosensors based on ferrocenyl and imine units, because this redox interaction would become a possible competition reaction. © 2019 Elsevier Ltd